Advancements of Biohydrogen Production Based on Anaerobic Digestion: Technologies, Substrates, and Future Prospects - Rossana Parra; Cristhian Chicaiza-Ortiz; Robinson J. Herrera-Feijoo; Diana Victoria Arellano-Yasaca; Lien-Chieh Lee; Roberto Xavier Supe-Tulcan; Jaime Marti-Herrero (Sci)
Population growth has significantly increased energy and resource demands, driving research toward cost-effective technologies that repurpose waste into alternative energy forms such as biohydrogen. This review aims to comprehensively evaluate biohydrogen production via anaerobic digestion, addressing gaps in previous studies focusing on a single sustainable development goal or limited environmental benefits. The methodology used the Scopus database with specific keywords, the Preferred Reporting Items for Systematic Reviews and Meta-Analyses protocol to screen relevant articles, and bibliometric analysis to delineate research directions from 2002 to 2024. Findings indicate that research on biohydrogen production via anaerobic digestion has grown exponentially over the past two decades, with increasing emphasis on advanced techniques, innovative reactor configurations, and diverse microbial consortia. Emerging trends, including the integration of artificial intelligence for process optimization and comprehensive life cycle assessments, suggest promising avenues for large-scale implementation. Anaerobic digestion-based biohydrogen production supports several Sustainable Development Goals (SDGs), including the ones related to clean energy (SDG7), SDG 13 (climate action), and SDG 12 (waste management), among others. Recent advancements are synthesized to provide a clear roadmap for future research toward sustainable energy solutions.